The link between the consumption of sweetened beverages and the development of overweight and obesity among students of the University of the West Indies, St. Augustine campus in Trinidad and Tobago - Sa'eed Halilu Bawa; Natalia Rupert; Marquitta Webb (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Many risk factors, which contribute to the development of overweight and/or obesity have been investigated and identified. However, one of the largest independent contributors to the obesity epidemic, which is often overlooked, is the increased consumption of sweetened beverages, particularly among the adolescents and young adults. Objective. The purpose of this study was to investigate the relationship between sweetened beverage consumption and the development of overweight and obesity among the students of The University of the West Indies, St. Augustine campus in the Republic of Trinidad and Tobago. Material and methods. A cross-sectional study design was used, with a non-probability sampling method. The target population were the students of the University of the West Indies, St Augustine aged ≥18 years of age. The research data were collected through the distribution of a self-administered questionnaire, which was completed by each participant while anthropometric and clinical measurements were completed by the researchers. A total of 161 questionnaires were distributed to the students of participants. Out of 161 questionnaires distributed, 137 were collected, but only 133 were fully completed, which gave a response rate of 83%. Statistical analyses were conducted using IBM SPSS Statistics 19.0 (IBM Corporation, Chicago, IL, USA). Results. 97.1% of the participants stated that they consumed sweetened beverages while only 2.9% said that they did not. Based on the results generated from chi-squared statistic test, there was no association between BMI and gender, age group, ethnicity, and the frequency of the consumption of sweetened beverages and their quantities. Conclusion. No association between the intakes of sweetened beverages and overweight and/or obesity was found among the participants, but a very high prevalence of the consumption of these beverages was observed in the subjects.